Fungos causadores de podridões pós-colheita em uvas apirênicas no pólo agrícola de Juazeiro - BA e Petrolina - PE - Camargo, Rubia Brito; Peixoto, Ana Rosa; Terao, Daniel; Ono, Elizabeth Orika [UNESP]; Cavalcanti, Leonardo Sousa (Univ Fed Rural Semi-arido-ufersa, 2011)
In Brazil, postharvest diseases caused by pathogenic microorganisms are a major problem that causes damage to around 80% of the total fruit production. In the lower middle Sao Francisco river valley numerous studies on identification and control of fungal diseases during postharvest of grapes are needed, in order to minimize losses in this step. In this context, bunches of seedless varieties 'Crimson', 'Sonaka'; 'Superior' and 'Thompson' were collected from July to November 2009, in order to identify and quantify the incidence of pathogenic fungi. The grapes were collected on five farms which specialize in the production of table grapes for export, all located in Juazeiro - BA and Petrolina - PE. During this period, 10 samples were taken. In the fruit farm five plants were used for sampling, and removal of two bunches of grapes per plant, totaling 10 bunches per variety. Subsequently, they were sent to the laboratory of Plant Pathology at UNEB/DTCS where they were placed separately in a moist chamber for 48 hours at an average temperature of 23 degrees C. After this period, isolations of berries and stems in Petri plates containing PDA - potato-dextrose-agar were carried out with 10 repetitions, which were placed on benches under laboratory conditions. From the 8th day on, the presence of Aspergillus niger, Alternaria alternata, Cladosporium herbarum, Lasiodiploidia theobromae was observed, which presented the highest incidence, as well as Rhizopus stolonifer, Penicillium expansum.

No Brasil, as doenças pós-colheita causadas por microorganismos fitopatogênicos se constituem num grave problema e apresentam danos em torno de 80% do valor total da produção de frutas. Na região do Submédio do Vale do São Francisco muitos estudos se fazem necessários para a identificação e controle de doenças fúngicas na pós-colheita de uvas, visando minimizar as perdas nesta etapa. Neste contexto, foram coletados cachos das variedades apirênicas Crimson, Sonaka, Superior e Thompson com o objetivo de identificar e quantificar a incidência de fungos fitopatogênicos no período de julho a outubro de 2009 em cinco propriedades especializadas na produção de uvas finas de mesa para exportação, localizadas nos municípios de Juazeiro - BA e Petrolina – PE. Neste período foram realizadas 10 coletas. No pomar foram utilizadas cinco plantas para amostragem, sendo retirados dois cachos por planta, totalizando 10 cachos por variedade. Posteriormente, estes eram enviados ao laboratório de Fitopatologia da UNEB/ DTCS onde foram colocados separadamente em câmara úmida por 48 horas a uma temperatura média de 23 ºC . Após este período foram realizados isolamentos de bagas e engaço em placas de Petri contendo meio BDA – batata-dextrose-ágar, com 10 repetições, sendo estas, colocadas em bancadas sob condições de laboratório. A partir do 8º dia foram constatadas as presenças de Aspergillus niger, Alternaria alternata, Cladosporium herbarum, Lasiodiploidia theobromae que apresentaram maior incidência e ainda, Rhizopus stolonifer e Penicillium expansum.
Survey of fungi causing postharvest rot in seedless grapes in agricultal polo of Juazeiro-BA and Petrolina-PE
Keywords: Patology; Phytopathogens; Aspergillus; Alternaria